Evaluation of probiotic and glutamine in ovo on broilers challenged with Salmonella Heidelberg - de Souza Oro, Camila [UNESP]; dos Ouros, Caio Cesar [UNESP]; Ribeiro, Gabriella Costa [UNESP]; Tertuliano dos Santos, Cauê Bastos [UNESP]; Okamoto, Adriano Sakai [UNESP]; Hataka, Alessandre [UNESP]; de Moraes, Gustavo Nunes [UNESP]; Milbradt, Elisane Lenita [UNESP]; Filho, Raphael Lúcio Andreatti [UNESP] (Elsevier, 2023)
Salmonella Heidelberg (SH) is a bacterium that causes great economic damage to Brazilian poultry production. The indiscriminate use of antibiotics in poultry farming induces resistance to this microorganism. In this way, natural products are alternatives for replacing antibiotics, also contributing to the maintenance of the intestinal health of birds. Thus, the objective of the experiment was to evaluate broiler chicken hatchability and anti-Salmonella effects of in ovo treatment with a Lactobacillus reuteri probiotic consortium and glutamine. The experimental design was completely randomized with seven treatments. The in ovo treatments evaluated (control, glutamine, probiotic, probiotic plus glutamine, and ceftiofur hydrochloride, and ceftiofur hydrochloride plus glutamine) were mixed with the vaccine against Marek's disease and infectious bursal disease. The exposure to SH occurred 24 h after chick placement. Data was subjected to analysis of variance, Tukey, and Dunn test, with a significance level of 5%. All treatments that received glutamine in ovo showed better (P < 0.05) hatchability. The treatment with the probiotic, with or without glutamine, showed a lower (P < 0.05) amount of SH when compared to the other treatments. Three days after exposure, the chicks that received the probiotic showed greater (P < 0.05) villus height and greater crypt depth in the duodenum, jejunum, and ileum compared to the chicks that received ceftiofur hydrochloride. Therefore, glutamine in ovo improved hatchability, while the probiotic in ovo reduced the amount of Salmonella Heidelberg, in addition to increasing the villus height and crypt depth in broilers.
Keywords: broiler; gut health; hatching; in ovo; salmonellosis